Production of actinide isotopes near θlab = 0∘ in multinucleon transfer reaction 238U + 248Cm - Yu Yang; Long Zhu; Zehong Liao; Zepeng Gao; Yueping Fang; Jun Su; Zhong Liu; Dongsheng Hou; Hao Huang; Cheng Li; Fengshou Zhang (Physics Letters B)
The multinucleon transfer reaction 238U + 248Cm is studied at incident energies Ec.m. = 898 and 800 MeV using the Isospin-dependent Quantum Molecular Dynamics model. In this work, we investigate the angular distribution of products and their correlations with incident energy, charge distribution fluctuations, and kinetic energy. At 898 MeV, the angular distribution of heavy actinide products peaks near the grazing angle, whereas at 800 MeV, it shifts near 0∘. Moreover, at 800 MeV, the proportion of isotopes emitted at forward angles increases with atomic number. These results suggest that current gas-filled recoil separators and velocity filters, which are highly effective for small-angle fusion-evaporation products, could be adapted for low-energy multinucleon transfer reactions. Given the challenges in the separation and identification of transfer products, the results of this study provide valuable guidance for future experimental investigations.